Penerapan Pidana Terhadap Terdakwa Tindak Pidana Menambang Terumbu Karang di Kawasan Konservasi - Putra Feli, Aidil; Fitriati, Fitriati; A. Kana, Philips (Universitas Ekasakti, 2023)
Law Number 1 of 2014 concerning Amendments to Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands, explicitly explains criminal sanctions for perpetrators of mining coral reefs. This research is Normative Juridical legal research. Criminal Application Against Defendant Mining Coral Reefs in Conservation Areas In Decision Number 73/Pid.B/2017/PN Sit the defendant was charged under Article 73 paragraph (1) letter a of Republic of Indonesia Law No. 27 of 2007 concerning Management of Coastal Areas and Small Islands. Decision Number 592/Pid.Sus/2019/PN Pdg defendant Risal Bin Olleng was proven to have jointly committed the criminal act of destroying coral reef ecosystems in a conservation area as well as defendant I. Usmanto PGL. Brother and defendant II. Muhammad Nur PGL. The act mentioned above has been legally and convincingly proven guilty of committing the criminal act of